Packaging. Requirements for measuring and verifying the four heavy metals and other dangerous substances present in packaging, and their release into the environment. Requirements for measuring and verifying dangerous substances present in packaging, and their release into the environment Part 2, (8th September 2004) - British Standards Institution,
No abstract available